Hypoglycaemic Properties of The Combination of Roselle Calyx (Hibiscus sabdariffa Linn.) and Stevia Leaves (Stevia rebaudiana B.) in Alloxan-Induced White Rats - Febriyanti, Raden Maya; Putri, Refitha Nurul; Diantini, Ajeng; Levita, Jutti (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Roselle (Hibiscus sabdariffa L.) and stevia (Stevia rebaudiana Bertoni) are known to contain phenolic compounds and flavonoids that act as antioxidants and are beneficial in lowering blood sugar levels. This study aimed to determine the phytochemical content and evaluate the hypoglycemic effects of a combined aqueous extract of H. sabdariffa and S. rebaudiana in a 3:1 ratio on diabetic rats. Aqueous extracts were prepared and analyzed for total phenolic and flavonoid contents using the Folin-Ciocalteu and aluminum chloride methods. Diabetes was induced in male Wistar rats by intraperitoneal injection of alloxan (235 mg/kgBW). Rats in the test groups received 500 or 1000 mg/kgBW of the combination, with blood glucose levels measured on the 0th, 7th, and 14th days post-treatment using a glucometer. H. sabdariffa, S. rebaudiana, and their combination contained total phenolic contents of 102.75, 188.053, and 118.856 mgGAE/g, respectively, and flavonoid contents of 3.099, 6.987, and 4.791 mgQE/g, subsequently. Administration of the combination extract at 1000 mg/kgBW showed the highest hypoglycemic effect, reducing blood glucose levels by 35.98% on the 14th day compared to the negative control (p<0.05). The combination of H. sabdariffa and S. rebaudiana extracts demonstrates significant hypoglycemic activity, attributed to their phenolic and flavonoid content.